Childhood vaccination coverage in Europe: impact of different public health policies. (3rd July 2019) - Bechini, Angela; Boccalini, Sara; Ninci, Alessandra; Zanobini, Patrizio; Sartor, Gino; Bonaccorsi, Guglielmo; Grazzini, Maddalena; Bonanni, Paolo
ABSTRACT: Introduction : Vaccination is a crucial tool for the primary prevention of infectious diseases. Thanks to widespread vaccination, in the last century smallpox has been eradicated, and the Americas and Europe have become polio-free. Areas covered : The aim of our study was to assess vaccination coverage in childhood up to booster preschool age in order to update the analysis on European trends of immunization coverage in the last nine years (2009–2017) and to assess the impact of different national policies on vaccine uptake. Expert opinion : Despite the good results, several EU countries are going through unprecedented outbreaks of vaccine-preventable diseases due to insufficient coverage. The increase of vaccine hesitancy has made it difficult to reach and maintain high rates of vaccination coverage. Enforcing mandatory vaccinations is one of the strategies adopted by some countries, like Italy and France, to increase coverage. However, each country should find the most suitable way to keep up with vaccination coverages according to own cultural and organizational background.